2014
DOI: 10.1164/rccm.201311-2023oc
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Survival after Extracorporeal Membrane Oxygenation for Severe Acute Respiratory Failure. The Respiratory Extracorporeal Membrane Oxygenation Survival Prediction (RESP) Score

Abstract: The RESP score is a relevant and validated tool to predict survival for patients receiving ECMO for respiratory failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
728
12
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 671 publications
(782 citation statements)
references
References 30 publications
33
728
12
9
Order By: Relevance
“…In the present case, the patient needed higher PEEP settings due to worsening oxygenation before ECMO introduction. In terms of timing of ECMO initiation, it seems ideal to start ECMO within 7 days from ventilator introduction based on the ELSO guideline12 and Respiratory ECMO Survival Prediction (RESP) score 14. In addition, as Goodman et al 4.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, the patient needed higher PEEP settings due to worsening oxygenation before ECMO introduction. In terms of timing of ECMO initiation, it seems ideal to start ECMO within 7 days from ventilator introduction based on the ELSO guideline12 and Respiratory ECMO Survival Prediction (RESP) score 14. In addition, as Goodman et al 4.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the mortality rate among patients with non‐pulmonary sepsis‐induced acute respiratory distress syndrome (ARDS) was higher than in patients with pulmonary sepsis‐induced ARDS 18, 19. Nesseler et al 19.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several predictive mortality risk scores to help clinicians target the patients most likely to benefit from ECMO have been proposed 18, 21, 22. Among these, age9, 18, 21, 22, 23, 24 and SOFA score21, 22, 23, 24 were found to be particularly closely associated with hospital mortality and were independent prognostic factors in ARDS patients receiving ECMO support.…”
Section: Discussionmentioning
confidence: 99%
“…Third, recent series and a randomized trial demonstrated better survival for patients receiving ECMO for severe ARDS [2][3][4]15]. The CESAR trial [3] evaluated a strategy of transfer to a single center which had ECMO capability while the patients randomized to the control group received conventional MV.…”
Section: Why Should Ecmo Be Initiated Rapidly In This Patient?mentioning
confidence: 99%